Continuous-wave yellow laser generation at 578 nm by intracavity sum-frequency mixing of thin disk Yb:YAG laser and Nd:YAG laser. (1st July 2017) - Ma, Gangfei; Yang, Jianming; Tan, Huiming; Tian, Yubing; Yao, Wenming; Ju, Qiaojun; Zhang, Long; Chen, Jiansheng; Wu, Xiaodong; Gao, Jing
Abstract: We report a continuous-wave yellow laser at 578 nm obtained by doubly resonant intracavity sum-frequency mixing of thin disk Yb:YAG laser and Nd:YAG laser with a LBO nonlinear crystal. Single-wavelength laser operation at 578 nm by using a silica etalon as a wavelength selector and dual-wavelength operation at 578 nm and 582 nm are obtained with maximum output powers of 100 mW and 136 mW, respectively. The single wavelength operating power stability value in 30 min was ~4.7%, which was improved ∼21.6%, compared with that of dual-wavelength operation. Highlights: A novel cw yellow laser at 578 nm obtained by SFG is proposed. Doubly resonant intracavity SFG is realized by a Z-type cavity. The power stability value is enhanced by inserting a solid etalon. The maximum output power of 136 mW is obtained.